2016
DOI: 10.1016/j.bbamem.2016.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Diphenylhexatriene membrane probes DPH and TMA-DPH: A comparative molecular dynamics simulation study

Abstract: Fluorescence spectroscopy and microscopy have been utilized as tools in membrane biophysics for decades now. Because phospholipids are non-fluorescent, the use of extrinsic membrane probes in this context is commonplace. Among the latter, 1,6-diphenylhexatriene (DPH) and its trimethylammonium derivative (TMA-DPH) have been extensively used. It is widely believed that, owing to its additional charged group, TMA-DPH is anchored at the lipid/water interface and reports on a bilayer region that is distinct from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 100 publications
2
71
0
2
Order By: Relevance
“…Steady-state anisotropy of the probe in non-organized systems such as in n-heptane reached values 0.001. In organized systems such as liposomes, DPH-TMA is oriented along the hydrocarbon chains 20 in which rotation is reduced and anisotropy is increased. With decreasing fluidity of the bilayer structure, anisotropy values increased from 0.195 (without cholesterol) to 0.265 (50 mol% of cholesterol) ( Fig.…”
Section: Effect Of Cholesterol On the Size Distribution Of Liposomes mentioning
confidence: 99%
See 2 more Smart Citations
“…Steady-state anisotropy of the probe in non-organized systems such as in n-heptane reached values 0.001. In organized systems such as liposomes, DPH-TMA is oriented along the hydrocarbon chains 20 in which rotation is reduced and anisotropy is increased. With decreasing fluidity of the bilayer structure, anisotropy values increased from 0.195 (without cholesterol) to 0.265 (50 mol% of cholesterol) ( Fig.…”
Section: Effect Of Cholesterol On the Size Distribution Of Liposomes mentioning
confidence: 99%
“…We tested the effect of lipid membrane fluidity on the final morphology of liposomes expressed as the size distribution, polydispersity, and lamellarity. Based on exact measurements of lipid membrane fluidity (polarization of fluorescence) we predicted the effect of this parameter on the critical size of disc micelle intermediates and therefore their tendency to vesiculate and form liposomes 3,19,20 . Experimental data were compared with theoretical prediction following from the model based on Helfrich bending energy and analyses of the energetics and thermodynamics of vesicle formation 15 .…”
Section: Introduction Of Microfluidic Mixing Technique Opens a New Domentioning
confidence: 99%
See 1 more Smart Citation
“…This difference is highlighted by the incubation time of the two probes used. It has been reported that the hydrophobic fluorophore DPH is located in the inner region of the phospholipid bilayer, whereas TMA-DPH is more hindered in translational and rotational motions compared to DPH [59]. Therefore, DPH estimates the motional order of the inner hydrophobic membrane region, while TMA-DPH senses changes in motional order at the interface region.…”
Section: Cell Membrane Motional Order Of Adherent Lx-2 Cellsmentioning
confidence: 99%
“…Em fase gel, com o maior alinhamento das caudas, o movimento restrito implica menor diferença entre as componentes emitidas (menor anisotropia), crescente de acordo com a fluidez das caudas e maior rotação da sonda. Pela baixa perturbação, a técnica vem sendo utilizada experimentalmente [35] e teoricamente ( [36], [37], [38], [39], [40], [41]).…”
Section: Figuraunclassified